Nonlinear dynamics and mechanisms of digital inclusive finance on county-level public services in China: Threshold and mediation analyses - Xin Huang; Feng Lan (PLoS ONE, 2025)
Counties, as fundamental administrative units in China, play a pivotal role in advancing digital inclusive finance and improving public services. Despite their significance in bridging regional disparities and promoting grassroots development, research focusing specifically on counties remains insufficient. This article aims to explore the relationship between digital inclusive finance and county-level public service quality by constructing a comprehensive evaluation system. Selecting data from 1445 counties across three regions of China between 2008 and 2022, public service quality across five dimensions—education, healthcare, ecology, municipal, and transportation facilities—is assessed through the entropy weighting method. Empirical analyses using threshold, intermediary, and moderation effect models reveal that digital inclusive finance enhances livelihood-related services but negatively affects infrastructure-related services. A “U-shaped” nonlinear trend is identified in the impact of credit depth, with the development of the primary industry mitigating negative effects. Mediation analysis shows that digital inclusive finance can improve public services through two pathways: boosting the tertiary industry and increasing financial institution loans. This article offers theoretical and practical guidance for integrating digital inclusive finance to enhance the quality and equity of county-level public services.